A case study on the impacts of advising on EFL teacher development - Esen, Metin (Universitas Ahmad Dahlan, 2020)
Advising in language learning is one of the new ways of creating aware, reflective, and autonomous learners in the area of Second Language Acquisition (SLA). Some language learning institutions help their learners with their learning issues through advising in Self-access Centres practices by advisors and teacher-advisors. This case study aimed at exploring the presence of advising in teacher development frameworks assessing various teacher skills and behaviours. The research also asked 12 teacher-advisors form Ankara YÄ±ldÄ±rÄ±m BeyazÄ±t University, School of Foreign Languages if they believed advising had an impact on their professional development. Both quantitative and qualitative data were collected from the participants through a 38-item questionnaire and a 10-question written interview. The analysis of the results suggested that teacher development frameworks directly or indirectly assessed some teacher behaviours that can also be attributed to a teacher, and teachers seemed to believe that the practice of advising had positive impact on their teaching skills.